Sulakhul Politics as a Result of Sultan Akbar's Reformist and Revolutionary Thought Amidst Hindu Domination in India - Nurdiana, Siti; M, Amril (Nizham Jurnal Studi Keislaman, 2024)
The heyday of the Mughal Empire began during the reign of Jalaluddin Akbar. At that time Islam was very developed despite being in the midst of a strong Hindu culture because Jalaluddin Akbar implemented a form of sulakhul politics (universal tolerance). This research aims to find out what made Islam very developed during the time of Sultan Akbar and how the sulakhul political policy. The method used in this research is library research or literature study. Sultan Akbar's policy was to create sulakhul politics (universal tolerance). This policy considers himself a king as well as a religious leader, so that Sultan Akbar has two equally high positions. Policies in the field of religion are by establishing a religious discussion forum called Ibadat Hana and also making the Din Ilahi movement as a medium of tolerance and moderation in religion.The greatest kings of the Mughal Dynasty were Sultan Akbar, Sultan Shah Jahan, and Sultan Aurangzib. Sultan Akbar is best known for his political and cultural accommodation of Islamic rule and Hindu society in India. Under his leadership, the Mughals managed to develop into a large dynasty. In addition, his most famous policies were the din ilahi movement and sulakhul politics where religious tolerance was highly emphasized and implemented during his reign.